ACHIEVEMENT OF COMPETENCY DURING PEDIATRIC ROTATION OF ANESTHESIOLOGY RESIDENTS ACCORDING TO THE EDUCATIONAL STANDARD OF ANESTHESIOLOGY IN FACULTY OF MEDICINE AIRLANGGA UNIVERSITY - Meilissa Eka Susanti; Arie Utariani; Elizeus Hanindito (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Background: The advancement and development of science and technology in the field anesthesiology and intensive therapy, has become the basis for the need of quality national guideline that is ethically and professionally accountable. This operational guideline can serve as a national guideline in providing anesthesia and intensive therapy services to patients. Until today, there is still no standardize educational evaluation for the pediatric division of anesthesiology to assess whether it is following the expected standards. Aim: To analyze the competency of anesthesiology residents in the pediatric division based on logbook according to the type of cases and procedures, and the number of patients based on the standard curriculum of the pediatric division of anesthesiology Surabaya. Methods: This study was an observational study with retrospective design, evaluating the competency of anesthesiology residents of Airlangga University in pediatric rotation according to the type of cases and procedures, and the number of patients treated and recorded in residents’ logbook based on the standard curriculum of the pediatric division of anesthesiology Surabaya. Data collection was performed by taking secondary data from April 2018-April 2020. Result: Median total of eletive cases during rotation and emergency cases during shift treated by anesthesiology resident of pediatric division was 9 (5-13) neonates, 35 (26-44) infants, and 56 (48-62) children. Target of neonates cases was achieved by 35%, infants by 100%, and children by 95% residents. Target of caudal anesthesia was achieved by 100%, inhalation induction by 55%, and IV line insertion by 100%. No resident achieved target for CVC insertion. Conclusion: A more formal and comprehensive guideline to standardize log case recording can be beneficial as it can evaluate residents based on the data collected electronically.